Improving the Ability of Deaf Students to Construct Subject, Predicate, Object, and Adverb Sentences Using Wordwall Media - Rimi Kalteza; Suparno Suparno (Journal La Edusci, 2026)
This study aims to improve the ability of deaf students to construct simple sentences using the Subject, Predicate, Object, and Adverb pattern through Wordwall media. The study was conducted with 10th grade deaf students at a State Special Needs School in Dumai City. This research employed Classroom Action Research using the Kemmis and McTaggart model, which consisted of planning, action, observation, and reflection stages. The research was implemented in three cycles. Data were collected through sentence construction tests, observation sheets, and documentation. The data were analyzed using qualitative and quantitative descriptive techniques by comparing students’ learning progress from the pre action stage to each cycle. The findings showed a gradual improvement in students’ ability to identify sentence elements and construct SPOK sentences. The average score increased from 20 in the pre action stage to 30 in Cycle I, then reached 70 in Cycle II, and improved further to 90 in Cycle III. The number of students who achieved the predetermined Learning Objective Criteria also increased from three students in Cycle I to six students in Cycle II and all nine students in Cycle III. These findings indicate that Wordwall media supported a more visual, interactive, and structured learning process for deaf students. The use of Wordwall helped students recognize sentence elements, arrange words into correct SPOK patterns, and construct simple sentences more accurately. Therefore, Wordwall media can be considered an effective learning medium for improving SPOK sentence construction skills among deaf students.